The moderating effect of financial literacy on the adoption of Fintech - Alpay, Cihan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
The emergence of new technologies has enabled the development of new business models in the financial services industry similar to other industries. Thanks to these new technologies and business models, Fintech is now capable of competing with traditional financial service providers. In this academic work, Fintech is defined as certain companies that provide financial products and services other than traditional financial service companies. The effect of selected risk and benefit factors on the Fintech adoption intention through perceived benefit and perceived risk was investigated within the scope of this research. Moreover, to what extent the financial literacy levels of the users affect their Fintech adoption intention was examined. Finally, it was investigated if the effect of perceived benefit and risk constructs on Fintech adoption intention differs significantly for current and potential Fintech users. The survey as part of this research was reached a total number of 389 participants. The results obtained in this research are believed to attract the attention of researchers working in this field, companies operating in the financial services industry as well as existing customers and potential users of Fintech.
Keywords: Financial services industry -- Technological innovations.; Financial services industry.